2021
DOI: 10.1159/000518618
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hepatitis B Virus Infection Markers among Patients of the Ibn Sina University Hospital Center (Rabat, Morocco)

Abstract: <b><i>Introduction:</i></b> Viral hepatitis B is a global scourge affecting millions of people worldwide. In Morocco, hepatitis B is considered a public health problem, and available data converge to consider Morocco as a country with intermediate endemicity. In the present study, we have planned to evaluate the HBV prevalence in Morocco on a large scale and to assess the prevalence of different serological markers for better management of this infection in Morocco. <b><i>Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
2
4
0
Order By: Relevance
“…Morocco is classified as a low HBV endemic area and the prevalence of co-infection among the cohort of HIV-infected individuals in our study (4.90%) was almost twice as high as in the general population [23]. The prevalence of HBV was 2.5% in our CG, which confirms previous Moroccan findings (1.5% among blood donors and 2.5% through patients referred to the Ibn Sina University Hospital Center of Rabat) [8,17] and those reported by countries with a low endemicity for HBV.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Morocco is classified as a low HBV endemic area and the prevalence of co-infection among the cohort of HIV-infected individuals in our study (4.90%) was almost twice as high as in the general population [23]. The prevalence of HBV was 2.5% in our CG, which confirms previous Moroccan findings (1.5% among blood donors and 2.5% through patients referred to the Ibn Sina University Hospital Center of Rabat) [8,17] and those reported by countries with a low endemicity for HBV.…”
Section: Discussionsupporting
confidence: 90%
“…Thus, HIV-1/HBV co-infection alters the natural progression of hepatitis B and complicates antiviral treatment [5]. According to WHO data, Morocco was ranked among the low-prevalence countries for HBV [6] with estimated prevalences ranging from 1.5% to 2.5% [7,8]. However, given that the frequency of HIV-1/HBV coinfection varies from 0% to > 28.4% in African countries [9], no study has investigated the possible association between HIV infection and the prevalence of HBV infection in Morocco.…”
Section: Introductionmentioning
confidence: 99%
“…Among females, five were antenatal mothers (4.1% of total study group). Similar preponderance of males is seen in studies such as Hamida et al, 13 while Borgaonkar and Shahapur, 12 and Feindiri et al, 14 show a female preponderance. There was no significant association between gender distribution and HBeAg positivity.…”
Section: Discussionsupporting
confidence: 78%
“…About 2.7 million (7.4%) of the 36.7 million people living with HIV (PLHIV) are also infected with hepatitis B virus (HBV) of which 71% co-infected patients are from sub-Saharan Africa (66). In Africa, the seroprevalence of HBV infection ranges from 3 to 20% (28). Several studies reported Morocco as low endemic region with seroprevalence around 1.8%, and the males showed higher prevalence than females in all the age groups, especially among aged 30-50 years (29).…”
Section: Hepatitismentioning
confidence: 99%
“…Pertussis is another VPD, which remains a concern in many regions despite vaccination (69). According to WHO, the prevalence of pertussis has decreased from 150,000 cases to 65,000 cases from 2019 to 2020 (28). Most cases of pertussis are among children <1 year old, however, adults are considered as the main reservoir of transmission of the disease to unvaccinated young children (30).…”
Section: Other Vaccine Preventable Diseasesmentioning
confidence: 99%